Comparative study between Brachiaria spp. and Pithomyces chartarum poisoning in cattle - Seixas, Josilene Nascimento; Pinto, Carlos Augusto; Rodrigues, Armindo; Tokarnia, Carlos Hubinger; França, Ticiana Nascimento; Graça, Flavio Augusto Soares; d´Avila, Mariana Sequeira; Peixoto, Paulo Vargas (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Seixas J.N., Pinto C.A., Rodrigues A., Tokarnia C.H., França T.N., Graça F.A.S., d´Avila M.S. & Peixoto P.V. [Comparative study between Brachiaria spp. and Pithomyces chartarum poisoning in cattle.] Estudo comparativo das intoxicações por Brachiaria spp. e Pythomyces chartarum em bovinos. Revista Brasileira de Medicina Veterinária, 38(Supl.2):1-10, 2016. Setor de Patologia Veterinária, Departamento de Medicina Veterinária, Universidade Federal de Lavras, Lavras, MG 37200-000, Brasil. E-mail: josiseixas@dsa.ufla.br Numerous photosensitization (FTS) outbreaks on Brachiaria spp pastures occur in Brazil, resulting in significant economic losses - especially due to the vast acreages of these grasses in the country. Although the link between the presence of saponins and the occurrence of FTS is already established, some authors still attribute those losses to sporidesmin poisoning, which is a fungal metabolite produced by Pithomyces chartarum. This study aimed to highlight the clinical and pathological changes of photosensitivity caused by saponins and sporidesmin, confronting data from literature with our own observations. The presented cases were originally from different farms located in Brazil, where cattle were kept in Brachiaria pastures, and in Portugal, where no Brachiaria species are present. The symptoms were quite similar, except for the frequent occurrence of colic, diarrhea and decreased productivity during early pithomycotoxicosis. Macroscopically Brachiaria spp poisoning often produces an intense yellow- -orange color in the liver, while pithomycotoxicosis predominantly induces chronic proliferative liver injury. Histologically the presence “foam cells” and birefringent crystals are indicative of Brachiaria spp poisoning while fibrosis and biliary hyperplasia correspond to major injuries of sporidesmin.